2014
DOI: 10.1007/s11356-014-3681-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and cultivation of xylanolytic and cellulolytic Sarocladium kiliense and Trichoderma virens from the gut of the termite Reticulitermes santonensis

Abstract: The purpose of this work was the isolation and cultivation of cellulolytic and xylanolytic microorganisms extracted from the gut of the lower termite Reticulitermes santonensis. Microcrystalline cellulose (with and without lignin) and beech wood xylan were used as diets instead of poplar wood in order to select cellulose and hemicellulose-degrading fungi. The strain Sarocladium kiliense (Acremonium kiliense) CTGxxyl was isolated from the termites fed on xylan, while the strain Trichoderma virens CTGxAviL was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
4
16
2
1
Order By: Relevance
“…Bacillus species isolate TC-DT13 thus can utilize less expensive substrates which induces the production of xylanases. Compared to other studies using this waste, such as those by Tarayre et al (2013), Guan, Zhao, Zhao, Wang, Huo, Cui, and Jiang (2016) and Ping et al (2018), the results obtained in this study demonstrated higher xylanase activity at the maximum xylanolitic levels identified in prior the previous studies were 44.3 U mL -1 , 52.94 U mL -1 and 57.25 U mL -1 , respectively, using wheat bran.…”
Section: Effect Of Agroindustry Wastes On Xylanase Production By Bacicontrasting
confidence: 65%
“…Bacillus species isolate TC-DT13 thus can utilize less expensive substrates which induces the production of xylanases. Compared to other studies using this waste, such as those by Tarayre et al (2013), Guan, Zhao, Zhao, Wang, Huo, Cui, and Jiang (2016) and Ping et al (2018), the results obtained in this study demonstrated higher xylanase activity at the maximum xylanolitic levels identified in prior the previous studies were 44.3 U mL -1 , 52.94 U mL -1 and 57.25 U mL -1 , respectively, using wheat bran.…”
Section: Effect Of Agroindustry Wastes On Xylanase Production By Bacicontrasting
confidence: 65%
“…Trichoderma reesei RUT C30, for instance, when grown on cellulose 1% (w/v) for 7 days, have shown maximal enzyme activity of 0.25 U.mL -1 (Jiang et al, 2011). Trichoderma virens CTGxAviL, also grown on -cellulose + xylan beechwood, after 3 days, have produced activities of 0.38 U.mL -1 (Tarayre et al, 2015). Other fungal strains, as Aspergillus awamori (Paredes et al, 2015), for instance, have also shown very low results when grown on agro-industrial residues.…”
Section: Determination Of Physico-chemical Properties Of Enzymesmentioning
confidence: 99%
“…However, many studies demonstrated that cellulolytic and hemicellulolytic enzymes from microorganism in termite gut is quiet rich [11] such as: 73% cellulases and xylanases were known in Microcerotermes sp. [27]; the series of cellulase in the foregut/salivary gland; and a rich diversity of derived GHFs in the hindgut. Of the various exoglucanases are undeniably the most diverse [23].…”
Section: Putative Alkaline Enzymes In the Gut Flora Of C Gestroi Termentioning
confidence: 99%
“…have wider optimal pH range of 5.0-10.0. In case of cellulolytic and hemmicellulolytic enzymes of Sarocladium kiliense and Trichoderma virens isolated from the gut of the lower termite, R. santonensis, optimal pH range was pH 9-10 [27]. In the higher termite, Nasutitermes corniger, pH of the gut reaches as high as 11 [10].…”
Section: Putative Alkaline Protease and Lipasementioning
confidence: 99%